The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/pssc.201510175
|View full text |Cite
|
Sign up to set email alerts
|

Growth of compressively‐strained GaN films on Si(111) substrates with thick AlGaN transition and AlGaN superlattice buffer layers

Abstract: In this paper, crack‐free GaN films with step‐graded AlGaN transition layer and AlGaN superlattice layer as buffer layers were grown on Si(111) substrate by metal‐organic chemical vapor deposition(MOCVD). The combination of both buffers effectively improves the properties of GaN layer. With the optimization of the buffer structures, high quality compressively‐strained GaN layers with thickness up to 3.6 μm have been obtained on Si(111) substrates (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Consequently, although a thick crack-free GaN film could be obtained by inserting the multi-layered LT-AlN buffer, it was not suitable for the preparation of HEMTs with strict GaN crystal quality requirements. (2) AlGaN buffer layers include step-like graded AlGaN [97] and linearly graded AlGaN structures [98,99], where the Al composition gradually changes from an AlN nucleation layer to GaN [100], the gradual change of the lattice constant and thermal expansion coefficient from AlN to GaN being achieved by the graded AlGaN buffer layer [101]. On the one hand, the AlGaN buffer layers between the AlN and the GaN introduce compressive stress during the growth process to compensate for the tensile stress generated during cool down from the growth temperature, improving the crystal quality and surface roughness of the GaN film [102,103].…”
Section: Buffer Layermentioning
confidence: 99%
“…Consequently, although a thick crack-free GaN film could be obtained by inserting the multi-layered LT-AlN buffer, it was not suitable for the preparation of HEMTs with strict GaN crystal quality requirements. (2) AlGaN buffer layers include step-like graded AlGaN [97] and linearly graded AlGaN structures [98,99], where the Al composition gradually changes from an AlN nucleation layer to GaN [100], the gradual change of the lattice constant and thermal expansion coefficient from AlN to GaN being achieved by the graded AlGaN buffer layer [101]. On the one hand, the AlGaN buffer layers between the AlN and the GaN introduce compressive stress during the growth process to compensate for the tensile stress generated during cool down from the growth temperature, improving the crystal quality and surface roughness of the GaN film [102,103].…”
Section: Buffer Layermentioning
confidence: 99%
“…In fact, there has always been much more interest in obtaining foreign semiconductor growth on Si substrates to realize optoelectronic integration . The successful and impressive story of III-nitrides heteroepitaxially grown on Si substrates is well known and has pushed forward the rapid progress of nitride-based light-emitting diodes and power electronics. For the growth of β-Ga 2 O 3 (an oxide semiconductor) on Si substrates, however, two issues must be addressed: (1) the large lattice mismatch and (2) the negative effect of the native amorphous oxide layer on the Si surface, which is usually formed in the very initial stage of oxide thin-film growth, resulting in the degradation of structural quality.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 15 ] obtained high‐quality GaN‐based wafers by growing three AlGaN buffer layers on a 4 inch Si substrate using metal‐organic chemical vapor deposition (MOCVD) technology, the buffer layers had a content gradient of 0.65/0.45/0.10 and a thickness of 200 nm. Pan et al [ 16 ] discovered that optimizing the number of layers in the gradient AlGaN buffer layer and the difference in Al content in the AlGaN superlattice layer can adjust the strain state of the GaN layer more efficiently, thereby improving the surface morphology and crystal quality of GaN. Shen et al [ 17 ] achieved the growth of 2 μm‐thick, crack‐free GaN thin films by introducing ultra‐thin AlN/GaN superlattice interlayers into the superlattices, they controlled the average Al content by varying the thickness of the superlattice AlN and GaN, and found that cracks could be suppressed more effectively if the optimal average Al content is less than 0.5.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [15] obtained high-quality GaNbased wafers by growing three AlGaN buffer layers on a 4 inch Si substrate using metal-organic chemical vapor deposition (MOCVD) technology, the buffer layers had a content gradient of 0.65/0.45/0.10 and a thickness of 200 nm. Pan et al [16]…”
mentioning
confidence: 99%